Emergent interactive effects of climate change and contaminants in coastal and ocean ecosystems - Hatje, Vanessa; Sarin, Manmohan; Sander, Sylvia G.; Omanović, Dario; Ramachandran, Purvaja; Völker, Christoph; Barra, Ricardo O.; Tagliabue, Alessandro (Frontiers in Marine Science, 2022)
The effects of climate change (CC) on contaminants and their potential consequences to marine ecosystem services and human wellbeing are of paramount importance, as they pose overlapping risks. Here, we discuss how the interaction between CC and contaminants leads to poorly constrained impacts that affects the sensitivity of organisms to contamination leading to impaired ecosystem function, services and risk assessment evaluations. Climate drivers, such as ocean warming, ocean deoxygenation, changes in circulation, ocean acidification, and extreme events interact with trace metals, organic pollutants, excess nutrients, and radionuclides in a complex manner. Overall, the holistic consideration of the pollutants-climate change nexus has significant knowledge gaps, but will be important in understanding the fate, transport, speciation, bioavailability, toxicity, and inventories of contaminants. Greater focus on these uncertainties would facilitate improved predictions of future changes in the global biogeochemical cycling of contaminants and both human health and marine ecosystems.